Pesquisa de Escherichia coli diarreiogênica em pontos de abastecimento de água para consumo georreferenciados, na mesorregião de Belo Horizonte, como modelo inovador de ação em Vigilância Epidemiológica - Mariana Moreira (2018)
The study was carried out with the objective of contributing to a better understanding of the vulnerability of the populations regarding the microbiological quality of drinking water in three municipalities of the mesoregion of Belo Horizonte - Ouro Preto, Mariana and Itabirito. One of the main results achieved was the mapping of the areas with the highest degree of contamination, highlighting the presence of Escherichia coli diarrheogenic pathotypes. A total of 1185 water samples were collected, according to the criteria established by Ministry of Health Ordinance No. 2914. Urban and rural water supply points were included. These points were defined by geoprocessing and made available in a database for Health Surveillance of Municipalities, offering support for public policies in preventive actions and containment of outbreaks. The present work resulted from the institutional partnership of UFMG, UFOP and FUNED. After a potability evaluation, the samples were cultured in MacConkey Agar for the isolation of E. coli using Colilert®. The isolated samples were evaluated by molecular genetic method to investigate pathogenicity markers that define the enteropathogenic (EPEC), enterotoxigenic (ETEC) and shiga-enterohemorrhagic toxin (STEC-EHEC) bacterial pathogens. The potability analyzes were validated by FUNED and monthly published in the GAL System of the SUS digital platform.The contaminated points were spatialized using the TerraView Geoprocessing software along with the the data were generated by PostgresSql, in addition to the statistical analysis of Kernel. In this way a database was generated generating the "digital maps" that show concentration gradients. This computational tool contributes to a geographic analysis of the problem of recurrent contamination of water in real time, making it possible to determine the points with the greatest potential for the development of diarrheal disease.